The Role of Effective Communication of Protocollerian Organizations in the Secretariat of the Regional People's Representative - Dipanegara, Romy; Djalil, Nur Alim; Sukmarini, Andi Vita (Journal La Sociale, 2023)
This research was carried out at the Wajo Regency DPRD Secretariat. Data collection was carried out through observation, interviews and documentation. Data were analyzed using descriptive analysis. Based on the results of field research regarding the role of the protocol section of the Wajo district DPRD secretariat in preparing the agenda for the Wajo district DPRD secretariat, it can be concluded that the role of the protocol and leadership communication section is not good and really needs to be improved, especially on the Problem-Solving Process Facilitator indicator. Problem Solving Process) and Communications Technician (Communications Technician). Some of the problems that arise are not just practical negligence of protocol, but include changes in the schedule, unpreparedness of the protocol apparatus in the field, the wishes of the leadership, lack of protocol competence, conditions at the event venue and other factors. However, due to the presence of alertness and good coordination so far, the gaps that have occurred can be resolved and do not cause significant qualitative problems using the interview method.